Composite additive for radioactive slurry solidification and radioactive slurry solidification method
By using composite additives of granulated blast furnace slag, zeolite and volcanic ash in radioactive mud treatment, combined with specific zeolite combinations and silicate cement, the problems of unstable performance of radioactive mud cured bodies and high nuclide leaching rate are solved, and high efficiency is achieved , low-cost radioactive mud curing meets strict performance standards.
Patent Information
- Application Number
- CN202411374285.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has problems such as unstable cured body performance, high nuclide leaching rate and high cost in the curing treatment of radioactive muds, and especially lacks effective treatment technology for radioactive muds.
Using a composite additive composed of granulated blast furnace slag, zeolite and volcanic ash, the zeolite adsorption capacity is improved by reducing the alkalinity of the hydration environment, combining zeolites with 8-10-membered cyclochazelite and 10-12-membered cycloclampetilite. Silicate cement and polycarboxylic acid-based water reducing agent were used to perform low-speed and high-speed stirring treatment to achieve curing.
The stable curing of radioactive mud was achieved, the nuclide leachation rate of 137Cs and 90Sr was reduced, the compressive strength and compactness of the cured body were improved, the performance requirements of GB/T14569.1-2011 was met, and the production cost was reduced.
Smart Images

Figure BDA0005068313340000101 
Figure BDA0005068313340000111 
Figure BDA0005068313340000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radioactive mud treatment, and in particular relates to a composite additive for radioactive mud solidification and a radioactive mud solidification method. Background Art
[0002] In the context of the increasing use of nuclear energy around the world, the safe treatment and disposal of radioactive waste has become an indispensable part of the sustainable development of the nuclear industry. Radioactive mud is a special type of waste generated during the operation of nuclear facilities, nuclear fuel cycles and emergency response to nuclear accidents. Its efficient and safe treatment technology is the key to ensuring environmental safety and public health. This type of waste not only contains highly radioactive nuclides, but may also carry harmful heavy metals, organic pollutants, etc., posing a long-term threat to the ecological environment. Therefore, it is particularly important to explore and optimize the treatment technology of radioactive mud, especially the solidification technology.
[0003] At present, the research directions of radioactive mud treatment technology in China mainly include glass solidification, steam reforming, cement solidification, etc. Glass solidification technology has the advantages of stable solidified body performance and low nuclide leaching rate, but it has disadvantages such as low waste inclusion rate, low production efficiency and high cost. It is generally used for the treatment of high-level waste liquid and α mud; steam reforming has the advantages of good volume reduction effect, stable solidified body performance and low nuclide leaching rate, but it is mainly used for inorganic treatment of organic waste and has no engineering application in radioactive mud cement solidification; cement solidification technology has the advantages of mature process, safety and reliability, low cost and high waste inclusion rate, and has been used for the solidification treatment of radioactive waste liquid; and there are few research and development and application precedents for the solidification treatment of radioactive mud at home and abroad.
[0004] With the advancement of nuclear facility decommissioning, the need for radioactive mud treatment is becoming increasingly urgent. Therefore, the development of radioactive mud cement solidification formula and matching additives is of practical significance for the proper treatment of such waste. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a composite additive for radioactive mud solidification.
[0008] In order to solve the above technical problems, the present invention provides the following technical solution: the composite additive comprises, by weight,
[0009] 80-100 parts of slag, 75-85 parts of zeolite, 75-85 parts of volcanic ash, 2-5 parts of water reducing agent;
[0010] The slag is granulated blast furnace slag, with a glass content of ≥95%, a magnesium oxide content of ≤4.0%, a sodium stearate content of 0.1% to 0.2%, and does not contain gypsum, sodium sulfate, or sodium thiosulfate;
[0011] It should be noted that the quality of slag on the market varies greatly, especially the low glass content. However, in order to sell the slag, stimulating materials such as sodium sulfate, sodium thiosulfate, and calcium sulfate are often added to accelerate the hydration process of the slag. These stimulating materials will promote the reaction between cement and organic matter in the mud, which can easily lead to poor stability of the solidified body, further increase the porosity of the solidified body, and reduce the resistance to leaching of radionuclides.
[0012] The granulated blast furnace slag used in the present invention has a glass content of ≥95%, a magnesium oxide content of ≤4.0%, a sodium stearate content of 0.1% to 0.2%, and does not contain gypsum, sodium sulfate, or sodium thiosulfate. This type of slag has high chemical activity. As a key component for regulating the hydration environment, after being added to the solidified body, it promotes the development of the solidified body's performance by reducing the alkalinity of the hydration environment, and establishes a stable adsorption environment for the solidification of the mud.
[0013] The zeolite is composed of 8-10-membered chabazite and 10-12-membered clinoptilolite, with a silicon dioxide content of ≥65%, a calcium oxide content of ≤5.0%, and a Si / Al ratio of 5-6;
[0014] It should be noted that traditional zeolites are mainly mordenite and clinoptilolite, which are mainly used for adsorption. 137 Cs, yes 90 The adsorption effect of Sr is not significant because the spatial structure of traditional zeolites is mainly composed of 8-membered rings with small exchange space volume, which cannot absorb ions with radii larger than 100 μm. 137 However, radioactive wastes involved in post-processing often contain 90 Elements with large ionic radius and easy hydrolysis, such as Sr, place higher requirements on the selection and compounding of zeolites.
[0015] The zeolite selected in the present invention is a mixture of (8-10)-membered chabazite and (10-12)-membered clinoptilolite, wherein the (8-10)-membered chabazite is added mainly for the purpose of adsorption. 137 Cs, and the addition of (10-12) membered clinoptilolite is mainly for the adsorption of 90Sr. This combination effectively improves the adsorption capacity of additives for different nuclides.
[0016] The volcanic ash has a silica content of ≥50% and a Si / Al ratio of 1 to 1.5;
[0017] It should be noted that when cement is used to solidify nitrate-containing waste and mud, due to the retarding effect and auxiliary plasticization of nitrate, water seepage or delayed water seepage often occurs. Water seepage is a phenomenon in which the liquid inside the solidified body floats up and further accumulates on the surface of the solidified body, which is a manifestation of poor uniformity of the solidified body. Water seepage is seriously harmful to the solidified body because the radioactive mud and waste liquid in the solidified body contain free 90 Sr and 137 When water seepage occurs, metal ions such as Cs will gather on the surface with the liquid. When the liquid evaporates and dries, these ions will remain on the surface of the solidified body, resulting in solidification failure. In order to prevent water seepage, the common practice is to add organic thickeners or reduce the water-cement ratio. However, organic thickeners will reduce the physical properties of the solidified body, and reducing the water-cement ratio will lead to insufficient inclusion rate of the solidified body or a heavy solidified product. High-quality volcanic ash is an ideal material for adsorbing the above ions. It can also fill the micropores of the solidified body, increase the density and viscosity of the solidified body, and further increase the ability to resist nuclide leaching while controlling water seepage.
[0018] The volcanic ash selected by the present invention has a silicon dioxide content of ≥50% and Si / Al≈(1-1.5). The hydration product generated by the volcanic ash participating in hydration has a stable structure and a large number of adsorption sites, which can further balance the hydration environment and reduce the interaction between radioactive mud and cement.
[0019] The water reducer is a polycarboxylic acid-based high-performance water reducer with an effective content of ≥95.
[0020] It should be noted that the water reducing agent selected in the present invention can effectively promote the compatibility of cement-mud and improve the workability of the solidified body.
[0021] As a preferred embodiment of the composite additive for radioactive mud solidification of the present invention, the ratio of 8-10-membered chabazite to 10-12-membered clinoptilolite in the zeolite is 2-3:7-8.
[0022] Another object of the present invention is to provide a method for solidifying radioactive mud.
[0023] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0024] Cement, composite additives as mixture I;
[0025] Radioactive mud, mixed with water as mixture II;
[0026] The mixture I and the mixture II are first stirred at a low speed and then at a high speed to obtain slurry I;
[0027] The slurry I is solidified to obtain solidified cement, thereby realizing the solidification method of radioactive mud.
[0028] As a preferred embodiment of the radioactive slurry solidification method of the present invention, the raw materials of the solidified cement are as follows:
[0029] 600-1200 parts of cement, 252-756 parts of composite additives, 0-473 parts of radioactive mud, and 200-400 parts of mixing water.
[0030] As a preferred embodiment of the radioactive slurry solidification method of the present invention, the cement comprises one of P·O42.5 ordinary silicate cement, P·I42.5 silicate cement, P·II42.5 silicate cement or P·II52.5 silicate cement.
[0031] As a preferred solution of the radioactive mud solidification method of the present invention, the water content of the radioactive mud is 60% to 70%, and the chemical composition includes NaNO3, Na2SO4, aminosulfonic acid or aminosulfonate.
[0032] As a preferred embodiment of the radioactive slurry solidification method of the present invention, the mixing water comprises tap water or medium or low radioactive level waste liquid with a sodium nitrate content of ≤330 g / L.
[0033] As a preferred solution of the radioactive mud solidification method of the present invention, the stirring speed of the low-speed stirring is 100-700 r / min, and the stirring time is 5-30 min.
[0034] As a preferred solution of the radioactive mud solidification method of the present invention, the stirring speed of the high-speed stirring is 701-2000 r / min, and the stirring time is 3-30 min.
[0035] As a preferred embodiment of the radioactive slurry solidification method of the present invention, the solidified cement obtained by the solidification method has a 28d compressive strength far exceeding the standard requirement of ≥7MPa; 137 The 42-day leaching rate and cumulative leaching fraction of Cs nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 4×10 -3 cm / d, cumulative leaching fraction ≤ 0.26cm; 90 The 42-day leaching rate and leaching fraction of Sr nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 1×10 -3cm / d, cumulative leaching fraction ≤0.17cm; the compressive strength after 90d immersion far exceeds the standard requirement of compressive strength loss rate ≤25%.
[0036] Beneficial effects of the present invention:
[0037] (1) The composite additive for solidifying radioactive mud of the present invention has an optimized formula. Specifically, granulated blast furnace slag is used as a key component for regulating the hydration environment. After being added to the solidified body, the alkalinity of the hydration environment is reduced to promote the development of the solidified body performance, thereby establishing a stable adsorption environment for the solidification of the mud.
[0038] The zeolite selected in the present invention is a mixture of (8-0)-membered chabazite and (10-12)-membered clinoptilolite, wherein the (8-10)-membered chabazite is added mainly for the purpose of adsorption. 137 Cs, and the addition of (10-12) membered clinoptilolite is mainly for the adsorption of 90 Sr. This combination effectively improves the adsorption capacity of additives for different nuclides.
[0039] The hydration product generated by the hydration of the volcanic ash selected in the present invention has a stable structure and a large number of adsorption points, which can further balance the hydration environment and reduce the interaction between the radioactive mud and cement;
[0040] The water reducing agent selected in the present invention can effectively promote the compatibility of cement-mud and improve the workability of the solidified body.
[0041] (2) In the radioactive mud solidification method of the present invention, common silicate cement on the market is used as the solidification base material. This type of cement is in sufficient supply, low in price, and easy to purchase. The present application can use medium and low-level radioactive waste liquid with a sodium nitrate content of ≤330g / L as mixing water, which can solidify the radioactive mud and the radioactive waste liquid at the same time, thereby improving production efficiency and reducing production costs. The present invention can achieve cement solidification of radioactive mud, and the mass inclusion rate reaches 0-20%, which is a pioneering technology.
[0042] (3) The 28d compressive strength of the solidified cement obtained by using the composite additive and solidification method of the present invention far exceeds the standard requirement of ≥7MPa; 137 The 42-day leaching rate and cumulative leaching fraction of Cs nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 4×10 -3 cm / d, cumulative leaching fraction ≤ 0.26cm; 90 The 42-day leaching rate and leaching fraction of Sr nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 1×10 -3cm / d, cumulative leaching fraction ≤0.17cm; the compressive strength after 90d immersion far exceeds the standard requirement of compressive strength loss rate ≤25%. The above performance not only meets the requirements of GB / T14569.1-2011 "Performance requirements for low and medium level radioactive waste solidification bodies - cement solidification bodies", but also provides a large space for accommodating engineering fault tolerance. DETAILED DESCRIPTION
[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0045] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0046] The radioactive mud used in the specific embodiment of the present invention is real radioactive mud from a certain facility. The water content of the radioactive mud is 60% to 70%, the concentration is about 1.1 to 1.3 g / mL, the pH is about 7 to 8, and the chemical composition is NaNO3, Na2SO4, aminosulfonic acid, aminosulfonate and radioactive nuclides. 90 Sr. 137 Cs, which has the same composition as the radioactive mud, will not affect the slurry I and the solidified body;
[0047] The slag used in the specific embodiment of the present invention is granulated blast furnace slag, wherein the glass content is 95%, the magnesium oxide content is 4.0%, and the sodium stearate content is 0.1% to 0.2%;
[0048] The zeolite used in the specific embodiment of the present invention is prepared by mixing chabazite and clinoptilolite in a ratio of 3:7, wherein chabazite is Ca[Al2Si4O 12 ]·6H2O, the crystal is a nearly cubic rhombohedron, and clinoptilolite is a 10-12-membered ring of Na(AlSi5O 12 )·4H2O, the crystals are flake or plate-like, and the aggregates are radial and hair-like; the silicon dioxide content is ≥65%, the calcium oxide content is ≤5.0%, and Si / Al≈(5-6);
[0049] The volcanic ash used in the present invention is crushed stone and mineral particles with a diameter less than 2 mm, wherein the silicon dioxide content is ≥50%, and Si / Al≈(1-1.5).
[0050] The polycarboxylate water reducer used in the present invention is a methyl methacrylate copolymer (polyester type polycarboxylate water reducer), wherein the methyl methacrylate copolymer content is ≥95%;
[0051] The silicate cement used in the present invention is P·O42.5 ordinary silicate cement (Southwest cement) with a compressive strength of 42.5 MPa.
[0052] The test method of the slurry fluidity in the present invention is carried out in accordance with JC / T986 "Cement-based Grouting Material":
[0053] Place a fluidity test mold in the center of a (600×600) mm glass plate, pour the stirred slurry into the test mold, wipe off the slurry that is above the test mold, and then gently lift the test mold vertically upward to allow the slurry to expand around under its own weight. After the expansion stops, use a steel ruler or vernier caliper to test the slurry diameter, which is used as the slurry fluidity test value;
[0054] The test method for the initial and final setting time of the slurry in the present invention is carried out in accordance with GB / T1346 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency":
[0055] Fill the test mold for setting time measurement with the slurry at one time, vibrate it several times and smooth the surface, then place it in a standard curing box (25℃±5℃, relative humidity ≥90%), and cure it until 30 minutes after the start of stirring, then measure for the first time whether the sample has initially set. After the sample has initially set, turn the test mold over and continue curing, and measure the final setting time until it is finally set.
[0056] The test method of the 28d compressive strength of the solidified body in the present invention is carried out with reference to GB / T17671 "Test method for strength of cement mortar (ISO method)":
[0057] The upper and lower surfaces of the solidified body obtained after curing for 28 days were properly polished with sandpaper to keep the surfaces parallel, and then the compressive strength was measured on a pressure testing machine.
[0058] The test method of the immersion loss rate of the solidified body in the present invention is carried out in accordance with GB / T14569.1 "Performance requirements for low and medium level radioactive waste solidified bodies - cement solidified bodies":
[0059] After 28 days of curing, the solidified body was tested by injecting deionized water into a 1000ml beaker and then immersing the sample in the beaker. After continuous immersion at (25±5)℃ for 90 days, observe whether the solidified block is broken. After taking out the solidified block and drying it in the shade, measure its compressive strength. Based on the 28d compressive strength, calculate the compressive strength loss rate before and after immersion.
[0060] The test method for the leaching performance of the solidified body in the present invention is carried out in accordance with GB / T7023 "Standard leaching test method for solidified bodies of low and medium level radioactive waste":
[0061] After the sample has been cured for 28 days, deionized water is first injected into a 1000ml polytetrafluoroethylene plastic container. A hook is set on the top cover of the container. The sample is tied with a nylon rope and hung on the hook on the top cover of the container. Finally, the top cover with the sample is tightened. When the sample is suspended, the distance between its surface and the inner wall of the container is ≥2cm. The timing starts from the sample immersion, and the deionized water is replaced at the cumulative leaching time of 24h, 3d, 7d, 10d, 14d, 21d, 28d, 35d and 42d. At the same time, the replaced deionized water is sampled and analyzed for the content of 90Sr and 137Cs. The leaching rate and cumulative leaching fraction corresponding to each age are calculated based on the content analysis results.
[0062] Example 1
[0063] This embodiment provides a composite additive for radioactive mud solidification and a radioactive mud solidification method, specifically:
[0064] 1) Prepare the composite additive according to the following mass parts;
[0065] 100 parts of slag, 75 parts of zeolite (chabazite: clinoptilolite = 3:7), 75 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0066] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0067] 1200 parts of Portland cement, 252 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0068] 3) Solidification of radioactive mud:
[0069] Portland cement and composite additives are mixed to obtain a mixture I;
[0070] Mixture I is added to a stirring pot, followed by radioactive mud and water;
[0071] The mixture was first stirred at a low speed for 5 min (135 r / min) and then at a high speed for 3 min (270 r / min) in a cement mortar mixer to obtain slurry I;
[0072] It was determined that the fluidity of slurry I in this embodiment was 163 mm, which met the fluidity requirements of the barrel curing process. The initial setting and final setting times of slurry I were 7 h and 8.5 h, respectively.
[0073] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0074] The compressive strength of the solidified body of this embodiment at 28 days was measured to be 17.82 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -39.11%, which meets the index requirement of the national standard GB14569.1-2011 that the loss rate is not greater than 25%.
[0075] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days;
[0076] Measured 137 The leaching rate of Cs on the 42nd day was 9.90×10 -5 cm / d, 42d cumulative leaching fraction is 7.61×10 -3 cm / d, 90 The leaching rate of Sr on the 42nd day was 7.64×10 -5 cm / d, 42d cumulative leaching fraction is 1.03×10 -2 cm, meeting the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d; 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days meets the standard 137 Cs is less than 0.26cm, other radionuclides (excluding 3 H) Less than 0.17 cm.
[0077] Example 2
[0078] The difference between this embodiment and embodiment 1 is that the mixing water in the adjustment step 2) is radioactive waste liquid, and the remaining steps and processes are all referred to embodiment 1 to obtain the slurry I and the solidified body of this embodiment.
[0079] It has been determined that the fluidity of slurry I in this embodiment is 172 mm, which meets the fluidity requirements of the barrel curing process. The initial setting and final setting times of slurry I are 7.6 h and 9.3 h, respectively.
[0080] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0081] The compressive strength of the solidified body of this embodiment at 28 days was measured to be 16.74 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -32.59%, which meets the index requirement of the national standard GB14569.1-2011 that the loss rate is not greater than 25%.
[0082] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days;
[0083] Measured 137 The leaching rate of Cs on the 42nd day was 1.12×10 -4 cm / d, 42d cumulative leaching fraction is 8.29×10 -3 cm / d, 90 The leaching rate of Sr on the 42nd day was 9.18×10 -5 cm / d, 42d cumulative leaching fraction is 1.21×10 -2 cm, meeting the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d; 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days meets the standard 137 Cs is less than 0.26cm, other radionuclides (excluding 3 H) Less than 0.17 cm.
[0084] Example 3
[0085] 1) Prepare the composite additive according to the following mass parts;
[0086] 100 parts of slag, 80 parts of zeolite (chabazite: clinoptilolite = 3:7), 80 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0087] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0088] 1000 parts of Portland cement, 452 parts of the composite additive of step 1), 473 parts of radioactive mud, and 300 parts of mixing water (radioactive waste liquid);
[0089] 3) Solidification of radioactive mud:
[0090] Portland cement and composite additives are mixed to obtain a mixture I;
[0091] Mixture I is added to a stirring pot, followed by radioactive mud and water;
[0092] The mixture was first stirred at a low speed for 10 min (140 r / min) and then at a high speed for 10 min (1000 r / min) in a cement mortar mixer to obtain slurry I;
[0093] It was determined that the fluidity of slurry I in this embodiment was 167 mm, which met the fluidity requirements of the barrel curing process. The initial setting and final setting times of slurry I were 7.2 h and 9.0 h, respectively.
[0094] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0095] The compressive strength of the solidified body of this embodiment at 28d was measured to be 21.15 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -28.66%, which meets the index requirement of the national standard GB14569.1-2011 that the loss rate is not greater than 25%.
[0096] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days;
[0097] Measured 137 The leaching rate of Cs on the 42nd day was 8.64×10 -5 cm / d, 42d cumulative leaching fraction is 7.94×10 -3 cm / d, 90 The leaching rate of Sr on the 42nd day was 7.79×10 -5 cm / d, 42d cumulative leaching fraction is 9.08×10 -3 cm, meeting the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d; 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days meets the standard 137 Cs is less than 0.26cm, other radionuclides (excluding 3 H) Less than 0.17 cm.
[0098] Example 4
[0099] This embodiment uses a 400L steel drum to conduct engineering scale verification of the test, specifically:
[0100] 1) Prepare the composite additive according to the following mass parts;
[0101] 100 parts of slag, 75 parts of zeolite (chabazite: clinoptilolite = 3:7), 75 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0102] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0103] 346.5 parts of Portland cement, 72.9 parts of the composite additive of step 1), 136.6 parts of radioactive mud, and 108.3 parts of mixing water (radioactive waste liquid);
[0104] 3) Solidification of radioactive mud:
[0105] Portland cement and composite additives are mixed to obtain a mixture I;
[0106] Mixture I was added into a 400L steel drum, followed by radioactive mud and water;
[0107] In the solidification stirring station, stir at a low speed for 20 min (70 r / min), and then stir at a high speed for 5 min (1100 r / min) to obtain slurry I;
[0108] It was determined that the fluidity of slurry I in this embodiment was 179 mm, which met the fluidity requirements of the barrel curing process. The initial setting and final setting times of slurry I were 6.8 h and 8.0 h, respectively.
[0109] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0110] The compressive strength of the solidified body of this embodiment at 28 days was measured to be 23.92 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -39.11%, which meets the index requirement of the national standard GB14569.1-2011 that the loss rate is not greater than 25%.
[0111] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days;
[0112] Measured137 The leaching rate of Cs on the 42nd day was 9.29×10 -5 cm / d, 42d cumulative leaching fraction is 8.47×10 -3 cm / d, 90 The leaching rate of Sr on the 42nd day was 7.90×10 -5 cm / d, 42d cumulative leaching fraction is 8.75×10 -3 cm, meeting the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d; 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days meets the standard 137 Cs is less than 0.26cm, other radionuclides (excluding 3 H) Less than 0.17 cm.
[0113] The test results of the solidified cement properties of Examples 1 to 4 are shown in Table 1.
[0114] Table 1
[0115]
[0116]
[0117] The above-mentioned Examples 1-2 illustrate the reliability and practicality of the present invention when the mixing water is changed from tap water to radioactive waste liquid. Because in practical applications, in order to reduce production costs, the feasibility of synergistic solidification of multiple radioactive wastes should be considered as much as possible. Therefore, if the compound additives and the solidification formula are not good, the goal of replacing the mixing water cannot be achieved. In Example 3 of the present invention, after the amount of additives is increased, even if the material radioactive waste liquid is used as mixing water, a solidified body with good performance can still be obtained, and the results show that even if the amount of cement is reduced, the performance of the solidified body prepared in Example 3 is not affected, and even some properties (such as 28d compressive strength, etc.) are improved to a certain extent. Example 4 is an engineering scale verification using a 400L steel barrel for testing. It can be seen that even if the additives and cement solidification formula are used under engineering conditions, the impact on the performance of the solidified body is minimal. These results all confirm the reliability and practicality of the present invention.
[0118] Comparative Example 1
[0119] The difference between this comparative example and Example 1 is that the formula of the composite additive is adjusted to:
[0120] 1) Prepare the composite additive according to the following mass parts;
[0121] 100 parts of slag, 75 parts of zeolite (chabazite: clinoptilolite = 3:7), 60 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0122] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0123] 1200 parts of Portland cement, 237 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0124] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0125] It was determined that the fluidity of slurry I in this embodiment was 170 mm, which met the fluidity requirements of the barrel curing process. The initial setting and final setting times of slurry I were 6.4 h and 7.3 h, respectively.
[0126] The 28d compressive strength of the cured product of this comparative example was measured to be 15.35 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -29.12%.
[0127] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 4.35×10 -3 cm / d, 42d cumulative leaching fraction is 2.63×10 -1 cm, 90 The leaching rate of Sr on the 42nd day was 1.53×10 -3 cm / d, 42d cumulative leaching fraction is 1.82×10 -1 cm, does not meet the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d; 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days does not meet the standard 137 Cs is less than 0.26cm, other radionuclides (excluding 3 H) Less than 0.17 cm.
[0128] Comparative Example 2
[0129] The difference between this comparative example and Example 1 is that the formula of the composite additive is adjusted to:
[0130] 1) Prepare the composite additive according to the following mass parts;
[0131] 100 parts of slag, 75 parts of zeolite (chabazite: clinoptilolite = 3:7), 90 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0132] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0133] 1200 parts of Portland cement, 267 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0134] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0135] It was determined that the fluidity of slurry I in this embodiment was 151 mm, which met the fluidity requirements of the barrel curing process. The initial setting and final setting times of slurry I were 4.2 h and 6.8 h, respectively.
[0136] The 28d compressive strength of the cured product of this comparative example was measured to be 11.24 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -35.28%.
[0137] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 5.41×10 -3 cm / d, 42d cumulative leaching fraction is 3.78×10 -1 cm, 90 The leaching rate of Sr on the 42nd day was 3.12×10 -3 cm / d, 42d cumulative leaching fraction is 2.74×10 -1 cm, does not meet the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d; 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days does not meet the standard 137 Cs is less than 0.26cm, other radionuclides (excluding 3 H) Less than 0.17 cm.
[0138] Table 2 Comparison of the performance of the solidified cement obtained in Comparative Examples 1 and 2 and the solidified cement obtained in Example 1
[0139]
[0140] It can be seen from Table 2 that when the amount of volcanic ash exceeds the scope of this application, the anti-leaching performance of the solidified body decreases. This is due to the occurrence of free liquid and salting out phenomena. This shows that volcanic ash needs to be controlled within a certain range to effectively inhibit the salting out of free liquid in the solidified body and the resulting nuclide diffusion to play a positive correlation role.
[0141] Comparative Example 3
[0142] The difference between this comparative example and Example 1 is that the formula of the composite additive is adjusted to:
[0143] 1) Prepare the composite additive according to the following mass parts;
[0144] 100 parts of slag, 60 parts of zeolite (chabazite: clinoptilolite = 3:7), 75 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0145] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0146] 1200 parts of Portland cement, 237 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0147] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0148] It was determined that the fluidity of slurry I in this comparative example was 175 mm, and the initial setting and final setting times of slurry I were 6.6 h and 7.8 h, respectively.
[0149] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0150] The 28d compressive strength of the cured product of this comparative example was measured to be 16.92 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -30.11%.
[0151] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 2.78×10 -4 cm / d, 42d cumulative leaching fraction is 2.12×10 -2 cm, 90 The leaching rate of Sr on the 42nd day was 1.72×10 -3cm / d, 42d cumulative leaching fraction is 1.92×10 -1 cm, does not meet the GB14569.1-2011 standard 90 Sr is less than 1×10 -3 cm / d requirement; the 42-day cumulative leaching fraction does not meet the requirements of other radionuclides (excluding 3 H) Less than 0.17 cm.
[0152] Comparative Example 4
[0153] The difference between this comparative example and Example 1 is that the formula of the composite additive is adjusted to:
[0154] 1) Prepare the composite additive according to the following mass parts;
[0155] 100 parts of slag, 90 parts of zeolite (chabazite: clinoptilolite = 3:7), 75 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0156] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0157] 1200 parts of Portland cement, 267 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0158] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0159] It was determined that the fluidity of slurry I in this comparative example was 160 mm, and the initial setting and final setting times of slurry I were 5.7 h and 8.2 h, respectively.
[0160] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0161] The 28d compressive strength of the cured product of this comparative example was measured to be 13.57 MPa, which meets the requirement of the GB14569.1-2011 standard that the compressive strength is greater than 7 MPa, and the compressive strength loss rate is -30.11%.
[0162] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 3.82×10 -4 cm / d, 42d cumulative leaching fraction is 4.17×10 -2cm, 90 The leaching rate of Sr on the 42nd day was 3.21×10 -3 cm / d, 42d cumulative leaching fraction is 2.84×10 -1 cm, does not meet the GB14569.1-2011 standard 90 Sr is less than 1×10 -3 cm / d requirement; the 42-day cumulative leaching fraction does not meet the requirements of other radionuclides (excluding 3 H) Less than 0.17 cm.
[0163] Table 3 Comparison of the performance of the solidified cement obtained in Comparative Examples 3 and 4 and the solidified cement obtained in Example 1
[0164]
[0165] It can be seen from Table 3 that when the zeolite dosage is lower than the minimum dosage or higher than a certain dosage, the prepared solid body has reduced resistance to nuclide leaching. This shows that the zeolite addition amount needs to be controlled within a certain range to play a positive role in improving the solid body's adsorption and solidification effect on nuclides.
[0166] Comparative Example 5
[0167] The difference between this comparative example and Example 1 is that the formula of the composite additive is adjusted to:
[0168] 1) Prepare the composite additive according to the following mass parts;
[0169] 70 parts of slag, 75 parts of zeolite (chabazite: clinoptilolite = 3:7), 75 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0170] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0171] 1200 parts of Portland cement, 222 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0172] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0173] It was determined that the fluidity of slurry I in this comparative example was 144 mm, and the initial setting and final setting times of slurry I were 5.9 h and 7.3 h, respectively.
[0174] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0175] The 28d compressive strength of the cured product of this comparative example was measured to be 4.96 MPa, which does not meet the requirement of the compressive strength greater than 7 MPa in the GB14569.1-2011 standard. The compressive strength loss rate was 25.77%, which does not meet the index requirement of the loss rate not greater than 25% stipulated in the national standard GB14569.1-2011.
[0176] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 4.99×10 -3 cm / d, 42d cumulative leaching fraction is 3.15×10 -1 cm, 90 The leaching rate of Sr on the 42nd day was 8.21×10 -4 cm / d, 42d cumulative leaching fraction is 1.09×10 -1 cm, does not meet the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days does not meet the standard 137 The requirement of Cs is less than 0.26cm.
[0177] Comparative Example 6
[0178] The difference between this comparative example and Example 1 is that the formula of the composite additive is adjusted to:
[0179] 1) Prepare the composite additive according to the following mass parts;
[0180] 130 parts of slag, 75 parts of zeolite (chabazite: clinoptilolite = 3:7), 75 parts of volcanic ash, and 2 parts of polycarboxylate water reducer.
[0181] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0182] 1200 parts of Portland cement, 282 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0183] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0184] It was determined that the fluidity of slurry I in this comparative example was 130 mm, and the initial setting and final setting times of slurry I were 6.2 h and 7.8 h, respectively.
[0185] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0186] The 28d compressive strength of the cured product of this comparative example was measured to be 6.45 MPa, which does not meet the requirement of the compressive strength greater than 7 MPa in the GB14569.1-2011 standard. The compressive strength loss rate was 30.24%, which does not meet the index requirement of the loss rate not greater than 25% stipulated in the national standard GB14569.1-2011.
[0187] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 3.89×10 -3 cm / d, 42d cumulative leaching fraction is 4.29×10 -1 cm, 90 The leaching rate of Sr on the 42nd day was 9.72×10 -4 cm / d, 42d cumulative leaching fraction is 3.54×10 -1 cm, does not meet the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days does not meet the standard 137 The requirement of Cs is less than 0.26cm.
[0188] Table 4 Comparison of the performance of the solidified cement obtained in Comparative Examples 5 and 6 and the solidified cement obtained in Example 1
[0189]
[0190] It can be seen from Table 4 that when the slag content exceeds the range of this application, the 28d compressive strength of the solidified body and the compressive strength loss rate after 90d immersion are greatly reduced, and the leaching value of the nuclides is significantly increased. This shows that the slag addition amount plays a positive correlation role in maintaining the hydration environment of the solidified body, improving the density of the solidified body and reducing the porosity within a certain range.
[0191] Comparative Example 7
[0192] The difference between this comparative example and Example 1 is that the number of parts of the composite additive in step 2) is adjusted to 189 parts, specifically:
[0193] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0194] 1200 parts of Portland cement, 189 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0195] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0196] It was determined that the fluidity of slurry I in this comparative example was 127 mm, the initial setting time and the final setting time of slurry I were 5.5 h and 6.7 h, respectively, and obvious free liquid and salt precipitation appeared on the surface of the solidified body after hardening.
[0197] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0198] The 28d compressive strength of the cured product of this comparative example was measured to be 3.44 MPa, which does not meet the requirement of the compressive strength greater than 7 MPa in the GB14569.1-2011 standard. The compressive strength loss rate was 56.94%, which does not meet the index requirement of the loss rate not greater than 25% stipulated in the national standard GB14569.1-2011.
[0199] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 1.12×10 -2 cm / d, 42d cumulative leaching fraction is 6.24×10 -1 cm, 90 The leaching rate of Sr on the 42nd day was 9.96×10 -3 cm / d, 42d cumulative leaching fraction is 7.79×10 -1 cm, does not meet the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d, 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days does not meet the standard 137 Cs is less than 0.26cm, other radionuclides (excluding 3 H) Less than 0.17 cm.
[0200] Comparative Example 8
[0201] The difference between this comparative example and Example 1 is that the formula of the composite additive is adjusted to:
[0202] The difference between this comparative example and Example 1 is that the number of parts of the composite additive in step 2) is adjusted to 315 parts, specifically:
[0203] 2) Prepare the raw materials of the solidified cement according to the following mass parts;
[0204] 1200 parts of Portland cement, 315 parts of the composite additive of step 1), 473 parts of radioactive mud, 375 parts of mixing water (tap water);
[0205] The remaining steps and processes are all referred to Example 1 to obtain the slurry I and the cured product of this comparative example.
[0206] It was determined that the fluidity of slurry I in this comparative example was 135 mm, the initial setting time and the final setting time of slurry I were 5.0 h and 6.2 h, respectively, and no obvious free liquid and salt precipitation appeared on the surface of the solidified body after hardening.
[0207] Transfer slurry I to The mold was vibrated and bubbles were driven out with a glass rod, then the mold was smoothed and placed in a curing box for curing. After curing for 48 hours, the mold was demoulded and cured for a total of 28 days to obtain a radioactive mud solidified body. The curing temperature was 25°C and the relative humidity was 90%.
[0208] The 28d compressive strength of the cured product of this comparative example was measured to be 5.84 MPa, which does not meet the requirement of the compressive strength greater than 7 MPa in the GB14569.1-2011 standard. The compressive strength loss rate was 42.98%, which does not meet the index requirement of the loss rate not greater than 25% stipulated in the national standard GB14569.1-2011.
[0209] Determine the cured product of this comparative example 137 Cs and 90 The leaching rates of Sr at 1, 3, 7, 10, 14, 21, 28, 35, and 42 days were measured. 137 The leaching rate of Cs on the 42nd day was 4.23×10 -2 cm / d, 42d cumulative leaching fraction is 5.36×10 -1 cm, 90 The leaching rate of Sr on the 42nd day was 7.45×10 -3 cm / d, 42d cumulative leaching fraction is 8.76×10 -1 cm, does not meet the GB14569.1-2011 standard 137 Cs is less than 4×10 -3 cm / d, 90 Sr is less than 1×10 -3 cm / d requirement; the cumulative leaching fraction for 42 days does not meet the standard 137 Cs is less than 0.26cm, other radionuclides (excluding3 H) Less than 0.17 cm.
[0210] Table 5 Comparison of the performance of the solidified cement obtained in Comparative Examples 7 and 8 and the solidified cement obtained in Example 1
[0211]
[0212] It can be seen from Table 5 that the mechanical properties and anti-leaching properties of the solidified body obtained by adjusting the amount of the composite additive are significantly reduced, which means that the amount of the additive plays a positive role in improving the structural stability and anti-leaching properties of the solidified body within a certain range.
[0213] In summary, the composite additive for solidification of radioactive mud of the present invention adopts granulated blast furnace slag as a key component for regulating the hydration environment. After being added to the solidified body, the development of the solidified body performance is promoted by reducing the alkalinity of the hydration environment, thereby establishing a stable adsorption environment for the solidification of the mud.
[0214] The zeolite selected in the present invention is a mixture of (8-10)-membered chabazite and (10-12)-membered clinoptilolite, wherein the (8-10)-membered chabazite is added mainly for the purpose of adsorption. 137 Cs, and the addition of (10-12) membered clinoptilolite is mainly for the adsorption of 90 Sr. This combination effectively improves the adsorption capacity of additives for different nuclides.
[0215] The hydration product generated by the hydration of the volcanic ash selected in the present invention has a stable structure and a large number of adsorption points, which can further balance the hydration environment and reduce the interaction between the radioactive mud and cement;
[0216] The water reducing agent selected in the present invention can effectively promote the compatibility of cement-mud and improve the workability of the solidified body.
[0217] In the radioactive mud solidification method of the present invention, common silicate cement on the market is used as the solidification base material. This type of cement is in sufficient supply, low price, and easy to purchase. The present application can use medium and low level radioactive waste liquid with a sodium nitrate content of ≤330g / L as mixing water, which can solidify the radioactive mud and the radioactive waste liquid at the same time, thereby improving production efficiency and reducing production costs. The present invention can realize cement solidification of radioactive mud, and the mass inclusion rate reaches 0-20%, which is an innovative technology.
[0218] The solidified cement obtained by using the composite additive and solidification method of the present invention has a 28d compressive strength far exceeding the standard requirement of ≥7MPa; 137 The 42-day leaching rate and cumulative leaching fraction of Cs nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 4×10 -3 cm / d, cumulative leaching fraction ≤ 0.26cm; 90 The 42-day leaching rate and leaching fraction of Sr nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 1×10 -3 cm / d, cumulative leaching fraction ≤0.17cm; the compressive strength after 90d immersion far exceeds the standard requirement of compressive strength loss rate ≤25%. The above performance not only meets the requirements of GB / T14569.1-2011 "Performance requirements for low and medium level radioactive waste solidification bodies - cement solidification bodies", but also provides a large space for accommodating engineering fault tolerance.
[0219] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A composite additive for radioactive mud solidification, characterized in that: The composite additive comprises, by weight, 80-100 parts of slag, 75-85 parts of zeolite, 75-85 parts of volcanic ash, 2-5 parts of water reducing agent; The slag is granulated blast furnace slag, the glass content of which is ≥95%, the magnesium oxide content is ≤4.0%, the sodium stearate content is 0.1% to 0.2%, and it does not contain gypsum, sodium sulfate, or sodium thiosulfate; The zeolite is composed of 8-10-membered chabazite and 10-12-membered clinoptilolite, with a silicon dioxide content of ≥65%, a calcium oxide content of ≤5.0%, and a Si / Al ratio of 5-6; The volcanic ash has a silica content of ≥50% and a Si / Al ratio of 1 to 1.5; The water reducer is a polycarboxylic acid-based high-performance water reducer with an effective content of ≥95.
2. The composite additive for radioactive mud solidification according to claim 1, characterized in that: In the zeolite, the ratio of 8-10-membered ring chabazite to 10-12-membered ring clinoptilolite is 2-3:7-8.
3. A method for solidifying radioactive mud, characterized in that: The composite additive according to claim 1 further comprises: Cement, composite additives as mixture I; Radioactive mud, mixed with water as mixture II; The mixture I and the mixture II are first stirred at a low speed and then at a high speed to obtain slurry I; The slurry I is solidified to obtain solidified cement, thereby realizing the solidification method of radioactive mud.
4. The method for solidifying radioactive mud according to claim 3, characterized in that: Calculated by mass percentage of the raw materials of the solidified cement, including: 600-1200 parts of cement, 252-756 parts of the composite additive according to claim 1, 0-473 parts of radioactive mud, and 200-400 parts of mixing water.
5. The method for solidifying radioactive slurry according to claim 4, characterized in that: The cement comprises one of P·O42.5 ordinary silicate cement, P·I42.5 silicate cement, P·II42.5 silicate cement or P·II52.5 silicate cement.
6. The method for solidifying radioactive mud according to claim 4, characterized in that: The water content of the radioactive mud is 60% to 70%, and the chemical composition includes NaNO3, Na2SO4, aminosulfonic acid or aminosulfonate.
7. The method for solidifying radioactive mud according to claim 4, characterized in that: The mixing water includes tap water or medium or low radioactive level waste liquid with a sodium nitrate content of ≤330g / L.
8. The method for solidifying radioactive mud according to claim 3, characterized in that: The stirring speed of the low-speed stirring is 100-700 r / min, and the stirring time is 5-30 min.
9. The method for solidifying radioactive slurry according to claim 3, characterized in that: The stirring speed of the high-speed stirring is 701-2000 r / min, and the stirring time is 3-30 min.
10. The method for solidifying radioactive slurry according to any one of claims 3 to 9, characterized in that: The solidified cement obtained by the method has a 28-day compressive strength far exceeding the standard requirement of ≥7MPa; 137 The 42-day leaching rate and cumulative leaching fraction of Cs nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 4×10 -3 cm / d, cumulative leaching fraction ≤ 0.26cm; 90 The 42-day leaching rate and leaching fraction of Sr nuclides are much lower than the standard requirement of 42-day leaching rate ≤ 1×10 -3 cm / d, cumulative leaching fraction ≤0.17cm; the compressive strength after 90d immersion far exceeds the standard requirement of compressive strength loss rate ≤25%.